Fifth Five Year Plan Draft Annual Plan 1977-78 - Planning Commission (Planning Commission, 1976)
When the Fifth Five-Year Plan started in 1974-75, Uttar Pradesh, with the rest of India, was passing through a period of great stress due to all-round shortages occasioned by unfavourable weather conditions during 1972-73 and 1973-74. The failure of rains, in the catchment area of Riband Dam, also resulted in the worsening of the already acute shortage of power in the State.
Uttar Pradesh Planning Department